2011
DOI: 10.1016/j.ijproman.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Risk ranking and analysis in target cost contracts: Empirical evidence from the construction industry

Abstract: The construction industry is often characterized by the traditional adversarial working relationships between contracting parties. There has been a strong call for applying target cost contracts to align the interest of owners and contractors together. By doing so, it aims to achieve a win-win situation under a partnering arrangement within the construction industry. Even though a multitude of research studies have been undertaken on target cost contracts (TCC) or guaranteed maximum price (GMP) contracts, not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 43 publications
3
81
0
4
Order By: Relevance
“…The t-test is commonly used to examine whether the mean values of a specific variable from two independent groups are significantly consistent, or whether they are significantly different [27,28]. The value of a parameter "Sig" needs to be established to indicate the level of difference between two groups of professionals about their perceptions of the importance of a specific variable.…”
Section: T-testmentioning
confidence: 99%
“…The t-test is commonly used to examine whether the mean values of a specific variable from two independent groups are significantly consistent, or whether they are significantly different [27,28]. The value of a parameter "Sig" needs to be established to indicate the level of difference between two groups of professionals about their perceptions of the importance of a specific variable.…”
Section: T-testmentioning
confidence: 99%
“…We hope that the research study will stimulate a wider debate on the underlying benefits associated with GMP/TCC in both local and international contexts for reference by the construction industry at large. Another research project focusing on risk identification, risk analysis, risk mitigation, and risk allocation inherent with GMP/TCC contracts have been completed recently in Hong Kong, Australia, and the United Kingdom (Chan et al, 2008b) and the key research findings have been reported in other publications (e.g., Chan et al, 2010a;2011c).…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al (2010b) reported on the major findings of a questionnaire survey on critical success factors in the implementation of TCC/GMP schemes in Hong Kong. Chan et al (2011a) ranked and analysed the key risks inherent with TCC/GMP contracts through an empirical survey in Hong Kong. In view of the viewpoints of the researchers mentioned above, the similar nature of TCC and GMP and the practices of previous research studies, TCC and GMP are put together for subsequent analyses and discussions in this paper.…”
Section: Concepts Of Tcc and Gmpmentioning
confidence: 99%
“…The interviewees suggested that the nature of variations, change in scope of works, quality and clarity of tender documents, unforeseen ground conditions, fluctuation of materials price, and approval from regulatory bodies for alternative cost saving designs, are the key risk factors inherent with TCC/GMP projects in Hong Kong . The results of the seven interviews also enabled the fine-tuning and confirmation of the 34 key risk factors sought from the literature review to be included on the empirical research survey questionnaire used in Hong Kong (Chan et al, 2011a).…”
Section: Structured Interviewsmentioning
confidence: 99%
See 1 more Smart Citation